2013
DOI: 10.3390/antibiotics2010115
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Risk Assessment for Human-Use Trimethoprim in European Surface Waters

Abstract: An environmental risk assessment (ERA) for the aquatic compartment in Europe from human use was developed for the old antibiotic Trimethoprim (TMP), comparing exposure and effects. The exposure assessment is based on European risk assessment default values on one hand and is refined with documented human use figures in Western Europe from IMS Health and measured removal in wastewater treatment on the other. The resulting predicted environmental concentrations (PECs) are compared with measured environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 114 publications
(205 reference statements)
2
35
0
Order By: Relevance
“…The stormwater-induced load peak might be an indication of the remobilization of sewer sediment and/or adsorbed substances, respectively. A load peak was also observed for trimethoprim which has low to moderate adsorption capability (Straub, 2013). In contrast, sulfamethoxazole is negatively charged at neutral pH and adsorption to particle matter might be insignificant (Tambosi et al, 2010) which, based on the absent load peak in June 2013, supports the assumption.…”
Section: Azithromycin Clarithromycin and Roxithromycinmentioning
confidence: 63%
“…The stormwater-induced load peak might be an indication of the remobilization of sewer sediment and/or adsorbed substances, respectively. A load peak was also observed for trimethoprim which has low to moderate adsorption capability (Straub, 2013). In contrast, sulfamethoxazole is negatively charged at neutral pH and adsorption to particle matter might be insignificant (Tambosi et al, 2010) which, based on the absent load peak in June 2013, supports the assumption.…”
Section: Azithromycin Clarithromycin and Roxithromycinmentioning
confidence: 63%
“…For example, subsequent to the evaluation of 22 antibiotics' effects on Lemna gibba (Brain et al ), Brain et al () demonstrated a <1% probability of encountering an antibiotic with toxicity below 1 µg/L in United States. By collating the exposure data of trimethoprim in Europe, the risk ratios of MEC50 to PNEC and MEC95 to PNEC were estimated to be 0.0024 and 0.025, respectively (Straub ). Although the ecological risks of antibiotics in China are generally characterized by calculating RQ based on the ratio of MEC to PNEC in a small‐scale river system, their findings in these studies are in consonance with the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The other antibiotics were exclusively dissolved. Some Kd values (L kg À1 ) in standard conditions at equilibrium were reported: 4.3 Â 10 2 for CIP, 5.0 Â 10 2 for NOR, 3.1 Â 10 2 for OFL and 2.3e6.3 Â 10 3 for TET (Tolls, 2001) and 2e3 Â 10 2 for TRI (Straub, 2013).…”
Section: Liquid/solid Phase Partitioningmentioning
confidence: 97%
“…The direct photolysis for environmental degradation of cephalosporins might be important in surface water bodies with depth 2e3 m (Fabbri et al, 2015). For TRI, an environmental half-life of 5.7 days was measured in freshwater and of 20 min under photodegradation (Straub, 2013).…”
Section: Antibiotic Dissipation Downstream Of the Wwtp Dischargementioning
confidence: 99%